Open Surgical Thrombectomy and Coronary Stent Placement for Treatment of Aortic Thrombotic Disease in a Bitch - dos Santos, Wisley Iemanjá Malaquias; Ferreira, Ariele Aparecida; Roman, Juliane Lais; Freitag, Flávio Augusto Vieira; Albernaz, Vinicius Gonzalez Peres; Castro, Jorge Luiz Costa; Carareto, Roberta; Dornbusch, Peterson Triches (Acta Scientiae Veterinariae, 2020)
Background: The thrombotic aortic disease in dogs and cats is characterized by the pathological formation of blood clots that can rupture and obstruct the blood flow. Abdominal ultrasonography can identify the location and extension of thrombus in the main vasculature and using the doppler it is possible to observe the blood flow around the thrombus. Stents are expandable tube-shaped endoprosthesis characterized as a metal mesh and used to prevent or repair stenoses, allowing liquid, gas, or solids to flow. This report aims to describe the surgical and medical treatment of aortic thrombotic disease followed by coronary stents placement in a bitch. Case: An 8-year-old Shih Tzu bitch, presented for evaluation of a 1-month progressive hind limbs paresis. Nociception was present in both limbs, but the patient presented discomfort and vocalization when manipulating the pelvic limbs. A complete blood count demonstrated anemia, mild neutrophilia, and lymphopenia. Serum biochemistry found an increase in ALT, ALP, blood urea nitrogen, and CK. Abdominal ultrasonography detected mild bulging of the caudal aorta and trifurcation of the iliac arteries. Increased intraluminal echogenicity and absence of blood flow were also detected using duplex doppler. The initial medical treatment was ineffective in improving clinical signs, therefore surgical repair was performed. The aorta was isolated and clamped with Satinsky forceps and incised. The thrombus fragmented during removal. A non-compliant high-pressure balloon was used to dilated and remove small fragments of blood clots from the right and left external iliac arteries. Coronary stents of 32 mm length by 2.75 mm diameter were placed to keep both iliac arteries free. Immediately after the procedure, there was a detectable distal pulse in both hind limbs. Despite intensive medical treatment, the patient evolved to respiratory distress and died on the sixth day after surgery. At necropsy, there were thrombi in the lumen of the arteries and several organs in addition to a large hyaline thrombus occluding 80-90% of the aortic lumen and left femoral artery. In the trifurcation region, clots were present, and stents placed in the iliac arteries were also occluded. Discussion: The occurrence of aortic and iliac thrombosis is associated with several conditions, including neoplasia, chronic kidney disease, heart failure, gastric dilatation-volvulus, hypothyroidism, and hyperadrenocorticism (HAC). In this case, the underlying cause of thromboembolism was supposed to be related to an endocrine condition, since the patient had clinical signs compatible with HAC; however, the low-dose dexamethasone suppression test was borderline and further examination could not be afforded. The diagnosis of thrombosis at the iliac trifurcation was obtained through ultrasonographic examination. Computed tomographic and nuclear resonance imaging could have been applied as well. The medical management of the thromboembolic disease was based on anticoagulant therapy with both heparin and clopidogrel in association with surgical thrombectomy and coronary stents placement. Despite the efforts, the patient died shortly after the surgical procedure, which was expected since high rates of mortality and morbidity is often related to the thromboembolic ischemia. The necroscopic examination of the animal found thrombi at the stents, cranial aorta, and microscopically in several tissues. The failure to directly treat the cause of the thrombus, which could not be diagnosed in time, may negatively interfered in patient survival time. The thrombectomy and coronary stents placement reestablished the femoral pulse immediately after surgery, which has been reported in other studies. The surgical resolution of aortic thrombus should be addressed in further studies.